Endoscopic Assessment of Colorectal Polyps - Pettis, Jaron; Paruch, Jennifer (Clinics in Colon and Rectal Surgery, 2023)
Colorectal cancer is the third most common cancer among men and the second among women. In the United States alone, there are 150,000 cases diagnosed each year. Colonoscopy remains the best method for identifying, evaluating, and intervening on patients with precancerous lesions. Multiple guidelines and techniques are available to assist the endoscopist with accurate diagnosis of these lesions. These include the Paris, Narrow-Band Imaging (NBI) International Colorectal Endoscopic (NICE), Japan NBI Expert Team (JNET), Kudo, Hiroshima, and Shudo classifications which utilize techniques such as chromoendoscopy, narrow-band imaging, and endocytoscopy to evaluate pit pattern and surface morphology. Utilization of these tools can help the endoscopist predict the cytology of a colonic lesion and select the most appropriate method for resection while maximizing organ preservation.
Keywords: endoscopy; classification; techniques; colon; polyp